Investigation of the Interphase Behavior of Different Bronze Alloys in Archaeological Soil of Cyprus - Doğru, Elif (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
The analysis of archaeological bronze artifacts for the identification of corrosion products and the evaluation of possible causes of these products is carried out by a combination of different disciplines. Corrosion products seen on bronze objects have often destructive effects on the artifacts due to their complex structure and put the artifacts in a cycle of irreversible deterioration. Because each artifact is original, it is necessary to examine each one separately in order to understand and stop the cause of this destructive process. In this thesis, it is aimed to identify corrosion products resulting from the chemical and electrochemical corrosion processes of the 6 bronze bowl, selected by hoard, in a pithos from Late Bronze Age and to explain the effect of environmental-structural factors. In line with this goal, Cyclic Voltammetry (CV) for electrochemical analysis of corrosion product samples, 3 of each and 18 total, and Fourier Infrared Spectroscopy (FT-IR) were used for spectroscopic examination. Electrochemical analyses and spectroscopic examinations of bronze artifacts have identified the presence of different types of copper alloy corrosion products. Consequently, corrosion types of 6 bronze bowls from the Late Bronze Age period were identified and it was observed that they were directly and indirectly related to environmental factors in the formation of these corrosion products. Keywords: bronze, corrosion, infrared spectroscopy, cyclic voltammetry

ÖZ Arkeolojik bronz eserlerin korozyon ürünlerinin tanımlanmasına yönelik analiz ve bu ürünlerin olası sebeplerinin değerlendirilmesi disiplinlerarası bir çalışma ile gerçekleştirilmiştir. Bronz objeler üzerinde görülmekte olan korozyon ürünleri kompleks yapıları sebebi ile eserler üzerinde çoğunlukla yıkıcı etkilere sahip olup, eserleri geri dönüşümü olmayan bir bozulma döngüsüne sokmaktadır. Her bir eserin özgün olmasından dolayı, bu yıkıcı sürecin sebebini anlamak ve durdurmak için detaylı araştırmalar yapılması gerekmektedir. Bu tezde, bir pitos içerisinde bulunan ve Geç Tunç Dönemi'ne ait altı adet bronz kasenin korozyon ürünleri iki farklı spektroskopik metot ile detaylı incelenmiştir.. Bu amaçla, altı farklı kaseden üçer örnek alınmak suretiyle toplam 18 adet korozyon ürünü örnekleri, Fourier Dönüşümlü Kızılötesi Spektroskopisi (FT-IR) ve Dönüşümlü Voltametri spektroskopik yöntemleri ile detaylı incelenmiştir. Elektrokimyasal analizleri ve spektroskopik incelemeleri gerçekleştirilmiş olan bronz eserlere ait örneklerde farklı türde, bakır alaşımlarına ait korozyon ürünlerinin varlığı belirlenmiştir. Geç Tunç Çağı dönemine ait altı adet bronze kasenin korozyon türleri tespit edilmiş ve bu korozyon ürünlerinin oluşumunda çevresel faktörler ile doğrudan ve dolaylı olarak ilişkisi detaylı olarak tartışılmıştır. Anahtar Kelimeler: bronz, korozyon, infrared spektroskopi, dönüşümlü voltametri
Master of Science in Chemistry. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2020. Co-Supervisor: Asst. Prof. Dr. Bülent Kızılduman, Supervisor: Prof. Dr. Huriye İcil.
Keywords: Chemistry Department; Bronze; corrosion; infrared spectroscopy; cyclic voltammetry